The Role of Cardiac Myosin Binding Protein C3 in Hypertrophic Cardiomyopathy‐Progress and Novel Therapeutic Opportunities. Issue 7 (16th February 2017) - Mohamed, Iman A.; Krishnamoorthy, Navaneethakrishnan T.; Nasrallah, Gheyath K.; Da'as, Sahar I.
Abstract : Hypertrophic cardiomyopathy (HCM) is a common autosomal dominant genetic cardiovascular disorder marked by genetic and phenotypic heterogeneity. Mutations in the gene encodes the cardiac myosin‐binding protein C, cMYBPC3 is amongst the various sarcomeric genes that are associated with HCM. These mutations produce mutated mRNAs and truncated cMyBP‐C proteins. In this review, we will discuss the implications and molecular mechanisms involved in MYBPC3 different mutations. Further, we will highlight the novel targets that can be developed into potential therapeutics for the treatment of HMC. J. Cell. Physiol. 232: 1650–1659, 2017. © 2016 Wiley Periodicals, Inc. Abstract : This review discusses the implications and the and molecular mechanisms of MYBPC3 different mutations. Further, we will highlight the novel targets that can be developed into potential therapeutics for the treatment of Hypertrophic cardiomyopathy.